Intercultural Awareness Through Indonesian Gastronomy with European Flavours in The Midst of Plurilingualism Political Framework - Asiati, Tri; Mujadid, Hammam; Adiarti, Dian; Wardani, Erna (Jurnal Lingua Idea, 2024)
In the midst of a multicultural society, cultivating intercultural awareness is a part of the political framework of plurilingualism, as European linguistic policy is based on a multilingual phenomenon. Plurilingualism is a renewal of the individual's ability to communicate on paralinguistic and paratextual aspects and develop intercultural skills, likely their cultural roots. This political hegemony unwittingly developed massively before the infiltration of French language in Indonesia through flavour contact in the form of gastro diplomacy. Starting with the European cookery heritage in Indonesia, this study aims to explore the presence of European flavours in culinary development to set up the attitudes of respect and understanding of the uniqueness of language culture based on French language learners. In addition to intercultural communication skills, this term contains nationalism as a political goal of plurilingualism, which ideally can eliminate cultural contestation. Therefore, the research methods are document studies, observations, and questionnaires, which aim to explore the existence of intercultural flavours as a form of cultural contact, authenticate cultural knowledge, build intercultural awareness, and diplomatic efforts from French language didactic. The result is a significant change, increasing interest in learning French, and also the development of national identity through knowledge, skills and behaviour as a part of intercultural awareness with authentic language materials.